A Global Review on the Biology of the Dolphinfish (Coryphaena hippurus) and Its Fishery in the Mediterranean Sea: Advances in the Last Two Decades. Issue 3 (2nd July 2020) - Moltó, Vicenç; Hernández, Pilar; Sinopoli, Mauro; Besbes-Benseddik, Amina; Besbes, Raouf; Mariani, Adriano; Gambin, Miriam; Alemany, Francisco; Morales-Nin, Beatriz; Grau, Antoni María; Camiñas, Juan Antonio; Báez, José Carlos; et al.
Abstract: The common dolphinfish ( Coryphaena hippurus ) is an epipelagic thermophilic species with a worldwide distribution in tropical and subtropical regions that is characterized by its migratory behavior and fast growth rates. This species is targeted by artisanal small-scale and recreational fisheries in most regions where it is found. This paper updates and analyzes the global scientific knowledge on the biology and ecology of this species, which was last revised at a regional level 20 years ago. This review showed an increase in knowledge about the population structure and regional differences in biological traits, in parallel with a notable lack of mechanistic and even empirical knowledge about the ecology of this species, which hampers a good understanding of the population dynamics and the potential impacts of environmental change. This paper also updates the information about the Mediterranean dolphinfish fishery, where the main four countries that exploit this species deploy 30% of fish aggregation devices (FAD) worldwide. The results suggest, among other effects, some temporal synchronicity in landings across countries, potential interannual stock movement affecting inter-country catches, diverging trends in prices and insufficient quality in the estimates of fishing effort. The authors propose a suite of specific measures to ameliorate this lack of knowledge and to better manage this complex living resource.